Dynamics of vegetative indexes on the background of complex therapy with inclusion of vegetotropic drugs among patients with bowels irritation syndrome - D. Yu. Latyshev (Бюллетень сибирской медицины, 2005)
Application of complex therapy with inclusion of vegetotropic drugs in treatment of patients with bowels irritation syndrome favors normalization of vegetative indexes among most of patients. At the same time effectiveness of the conducted therapy depends from initial indexes of vegetative activity.